Día de Muertos números = A Day of the Dead counting book - Tonatiuh, Duncan (Abrams Appleseed, 2023)
"Item by item, a family assembles a Day of the Dead altar to honor the memory and welcome the spirit of a loved one. Award-winning author-illustrator Duncan Tonatiuh draws on his own life experiences to create this bilingual counting book" --